Continuous erector spinae plane block for postoperative analgesia of multiple rib fracture surgery: case report - Yayik,Ahmet Murat (2019)
Abstract Introduction: The erector spinae plane block is a newly described and effective interfascial plane block for thoracic and abdominal surgery. This case report describes a patient with multiple rib fractures undergoing ultrasound-guided continuous erector spinae plane block for analgesia. Case report: A 37-year-old male patient was taken for surgical fixation of multiple rib fractures. At the end of the surgery, using ultrasound-guided longitudinal parasagittal orientation 3 cm to the lateral aspect of the T5 spinous process and an in-plane technique, 20 mL 0.25% bupivacaine was administered between the erector spinae muscle and the transverse process, and a catheter was then inserted in the same plane. Before the end of surgery, 1 g paracetamol and 50 mg dexketoprofen were administered. Postoperative analgesia was applied with patient controlled analgesia method using 0.25% bupivacaine via the catheter. The patient's Visual Analogue Scale score at rest in the first 24 h was 0. The patient was monitored for 3 days with Visual Analogue Scale < 4, and the catheter was removed on postoperative day 4. No opioid requirement other than paracetamol and dexketoprofen occurred during this time. No postoperative complications were recorded. Discussion: The erector spinae plane block is an alternative to paravertebral, intercostal, epidural or other regional techniques. It may be a suitable technique in anesthesia and algology practice due to providing analgesia in the postoperative period with a catheter in the erector spinae plane.